Domestic cat hepadnavirus associated with hepatopathy in cats: A retrospective study. (24th August 2022) - Piewbang, Chutchai; Dankaona, Wichan; Poonsin, Panida; Yostawonkul, Jakarwan; Lacharoje, Sitthichok; Sirivisoot, Sirintra; Kasantikul, Tanit; Tummaruk, Padet; Techangamsuwan, Somporn
Abstract: Background: Whether domestic cat hepadnavirus (DCH) infection is associated with clinical disease remains to be determined. Objectives: To determine the relationship between DCH detection, hematology, serum bichemistry and liver histology in DCH‐positive cats. Animals: One thousand twenty‐two cats in Thailand without concurrent diseases and not undergoing treatments adversely affecting the liver. Methods: Retrospective cross‐sectional study. Samples derived from cats with concurrent virus detection were excluded. DCH detection was determined in blood and fresh‐frozen liver by quantitative polymerase chain reaction (qPCR) and further investigated in liver sections showing histological parenchymal disorders (HPD) and normal liver (HNL) using in situ hybridization (ISH). Proliferative/apoptotic activities were determined using immunohistochemistry and ISH panels. Biochemical variables and risk factors for DCH infection were investigated. Results: Six hundred sixty‐one (557 blood and 119 liver samples) cats were included. DCH was detected in 18.50% (103/557), 13.85% (9/65), and 3.70% (2/54) of the blood, HPD, and HNL groups, respectively. Cats with DCH revealed abnormally high activity of aspartate aminotransferase (AST) ( P = .001) and alanine aminotransferase (ALT) ( P < .001). Among DCH‐positive HPD case 2/9 an 7/9 were acute and chronic hepatitis, of which 4/7 had hepatitis. Log viral copy number (LVCN) was positively correlated with ALT ( P < .001), triglyceride ( P < .001), and gamma‐glutamyl transpeptidase (GGT) ( P = .022). The LVCN also had a positive association with degree of hepatitis ( P < .05). There was hepatocyte proliferation activity in DHC positive cats. Conclusion and Clinical Importance: Domestic cat hepadnavirus infection was associated with high serum activity of liver enzymes and chronic lymphoplasmacytic hepatitis (LPH).